Simulation of herding behaviour in panic evacuation from a room with two exits. (2016) - Tan, Victor; Au, ChiKit
Herding behaviour is typically shown in most panic crowd evacuation and it always causes disastrous outcomes due to the slow evacuation. Simulations of panic crowd evacuation from a room with two exits by using a crowd of particles are presented in this article. A panic crowd is characterised by higher moving speed and smaller inter-particle distance and the congestion at the exit is mainly caused by these factors. The particles move with an even high speed because of the congestion. This is a positive feedback mechanism and the herding behaviour arises at the exit with heavy congestion. Eventually, all the particles select the highly congested exit. This article also discusses how the space time of a particle is affected by the congestion and the herding behaviour is initiated.